2022
DOI: 10.1177/13596535211062396
|View full text |Cite
|
Sign up to set email alerts
|

The transformation of HIV therapy: One pill once a day

Abstract: A co-formulated, one pill once a day antiretroviral regimen (single-tablet regimen), containing efavirenz, emtricitabine, and tenofovir disoproxyl fumarate ( Atripla), revolutionized the antiretroviral therapy landscape. Single-tablet regimens provide not only dosing convenience but help optimize adherence and persistence with antiretroviral therapy to achieve durably suppressed viremia with both individual and societal benefits. Given the many excellent options available now, single-tablet regimens are the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…[4][5][6] In most cases, singletablet regimens are prescribed because they reduce regimen complexity, improve adherence, and maintain viral load (VL) suppression (ie, noninferior to comparator arms). 7 Different combinations of ARV drugs are available for the treatment of HIV infections. 4,5,[8][9][10][11][12][13][14] BIC/FTC/TAF is one of newest single-tablet regimens available and is recommended for initial therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] In most cases, singletablet regimens are prescribed because they reduce regimen complexity, improve adherence, and maintain viral load (VL) suppression (ie, noninferior to comparator arms). 7 Different combinations of ARV drugs are available for the treatment of HIV infections. 4,5,[8][9][10][11][12][13][14] BIC/FTC/TAF is one of newest single-tablet regimens available and is recommended for initial therapy.…”
Section: Introductionmentioning
confidence: 99%
“…4-6 In most cases, single-tablet regimens are prescribed because they reduce regimen complexity, improve adherence, and maintain viral load (VL) suppression (ie, noninferior to comparator arms). 7…”
Section: Introductionmentioning
confidence: 99%
“…This lack of efficacy may contribute to explain why studies that investigated HIV were conducted in a well-defined period and stopped after 2006. Not to mention the introduction of the first triple combination of antiretroviral drugs in a single tablet, a fundamental step toward an effective and generally well-tolerated option for the management of HIV infection [ 67 ], that may have caused an interest loss in searching for supplemental treatments for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed the efforts to design antiretroviral regimens that are still effective and relatively safe from drug side effects. One of these approaches is the simplification of the multi-tablet regimen to a single tablet regimen that people living with HIV only take one dose of a single tablet per day [16,17]. Another study stated there was a significant relationship between the use of a single tablet regimen and a high level of adherence to antiretroviral therapy [18,19].…”
Section: Introductionmentioning
confidence: 99%